A Developed Realistic Urban Road Traffic in Erbil City Using Bi-directionally Coupled Simulations - Saad Talib Hasoon; Muhammed A. Mahdi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Internet of Vehicles (IoV) is increasingly brought to light last years. It has an impact to improve the transportation system in smart cities. It is a big umbrella of VANET. IoV has contributed in changing the transportation system since the emergence of smart vehicles. Due to Internet service availability data can smoothly be shared among vehicles. There are three scenarios to utilize the IoV services; these are urban, rural and highway scenarios. One of the main challenges in IoVs is how to simulate Inter Vehicles Communication (IVC) in a realistic simulation. This paper will present a proposed realistic urban traffic simulation in Erbil city using bi-directionally coupled simulations. A real map of the city has been involved to simulate the traffic of vehicles; while the Simulation of Uraban MObility (SUMO) is used to simulate the road traffics, its output would be used as input to the VEhicle In Network Simulation (VEINS) framework to simulate the network under OMNeT++ environment. On the other hand, data is shared between vehicles and roadsides to test the simulation. The results of the simulation have been analyzed in the last stage.